IMPACTUL COMUNICĂRII POLITICE PRIN NEW MEDIA ASUPRA DEMOCRAȚIEI (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The Impact of Political Communication through New Media over DemocracyThere are many studies of the impact of the new media in political communication as an inexhaustible source of information, and which facilitate the shifting of Internet users between the political or creative receiver of democracy and democracy. Researchers ask whether the use of new media in disseminating the political message influences the degree of social and civic involvement of the individual or communities online. In other words, greater access to the Internet and digital political communication stimulate democracy or increase social manipulation?